Evaluation of Biomarkers in Workers Exposed to Air Pollutants in Oil Refineries - Esraa H. mohammed; Adel M. Rabee (Institute of Medico-legal Publications Pvt Ltd, 2022)
Air pollution is nowadays a complex problem due to industrial prosperity. Among the chemical industry,oil refineries have been identified as major emitters of a wide range of pollutants, the workers of the oilrefinery are exposed to a great variety of toxic compounds. Air pollution is the main environmental causeof human disease and death. Therefore, it is necessary to develop early warning signals or biomarkersthat convincingly reflect adverse biological responses towards anthropogenic environmental toxinseven at minute concentrations. This work aims to study the effects of exposure to the air pollution of oilrefinery, on the parameter blood, TNF-a, antioxidant glutathione peroxidase(GPx), and oxidative stressmalondialdehyde (MDA), in workers of the oil refinery. Results showed that exposure to air pollutionin the oil refinery lead to( a significant increase in levels Hb, WBC, Lymphocyte, TNF-a, and MDA,decrease levels of GPx) P<0.05. And non –significant in( RBC, HCT, Neutrophils ) P>0.05 in workers,compared to healthy control.